Advances in Genomic Discovery and Implications for Personalized Prevention and Medicine: Estonia as Example - Prins, Bram Peter; Leitsalu, Liis; Pärna, Katri; Fischer, Krista; Metspalu, Andres; Haller, Toomas; Snieder, Harold (Journal of personalized medicine, 2021)
The current paradigm of personalized medicine envisages the use of genomic data to provide predictive information on the health course of an individual with the aim of prevention and individualized care. However, substantial efforts are required to realize the concept: enhanced genetic discoveries, translation into intervention strategies, and a systematic implementation in healthcare. Here we review how further genetic discoveries are improving personalized prediction and advance functional insights into the link between genetics and disease. In the second part we give our perspective on the way these advances in genomic research will transform the future of personalized prevention and medicine using Estonia as a primer.